Cycad forensics: tracing the origin of poached cycads using stable isotapes, trace element concentrations and radiocarbon dating techniques - Retief, Kirsten (Percy FitzPatrick Institute of African Ornithology, 2014)
In South Africa, the greatest threat to cycad populations is the illegal removal of wild plants for landscaping purposes and collector's gardens, resulting in declining populations that are already threatened with extinction. Radiocarbon dating in conjunction with stable isotopes and trace element concentrations could provide the essential evidence needed in court when prosecuting poachers and collectors. The aim of this study was to determine the feasibility of using radiocarbon dating, stable isotopes and trace element concentrations to identify specimens removed from the wild. To test this method, we sampled two individuals of Encephalartos lebomboensis and E. arenarius, with known wild origins and relocation histories (1946 and 1992 respectively), and compared these to individuals from the same wild location that had not been relocated (controls). Vascular rings were sampled using an increment corer from the upper, middle and lower sections of the cycads, which were cut into sections so that the inner, middle and outer rings for each core could be sampled. These samples were reduced to cellulose for δ18O and δ13C isotope analysis. Leaf bases were sampled from the upper, middle and lower sections of the cycad stem using a hammer and chisel, and petioles were cut from the cycad to represent the most recent growth. These samples were analysed for the following stable isotopes δ13C, δ15N, δ34S, 87Sr/86Sr, 206Pb/207Pb and 208Pb/207Pb, and the concentration of trace elements were analysed for the leaf bases. The means and variance were compared between the relocated and control specimens and a principal component analysis was done. The radiocarbon ages of E. lebomboensis tissues were more recent than expected, dating from 2006 to 1979, suggesting that this method would only be appropriate for specimens relocated within the past 6 to 30 years. Consistent with this, our δ18O and δ13C in cellulose, as well as the δ34S,87Sr/86Sr ratio and principal component analysis indicated that the relocated E. lebomboensis specimen (relocated 66 years ago) was significantly different from the control, implying that the stem of the relocated specimen did not grow in the wild. In contrast, the relocated E.arenarius specimen (relocated 20 years ago) was isotopically indistiguishable from the control in older tissues indicating a common origin, but was significantly different for the upper leaf bases, as well as a shift in δ18O cellulose for the upper vascular rings, indicating that the plant has been relocated. Thus, the use of radiocarbon dating and stable isotopes showed great potential as a forensic technique for cycads and suggestions for future development of this technique are given.